Lead in painted surfaces and dusts from rented urban properties (Plymouth, UK). (1st January 2023) - Tooms, Sarah; Stokes, Alison; Turner, Andrew
Abstract: X-ray fluorescence (XRF) spectrometry has been used to measure lead (Pb) in painted surfaces and indoor dusts from 14 rented properties in the city of Plymouth, UK. Lead was detected in 78 out of 164 surfaces measured (and in 69 out of 150 interior surfaces) with an overall median concentration of 7100 mg kg −1 (range from 157 to 139, 000 mg kg −1 ), and was detected in all but two properties that included one building constructed within the last 25 years. Selected measurements on an area basis ( n  = 48) returned Pb concentrations ranging from below 0.01 to 16.1 mg cm −2 that were significantly correlated with concentrations on a mass basis but with scatter that was attributed to the degree to which leaded paint had been overpainted. As potential measures of Pb exposure, mean concentrations in samples of lint ( n  = 8) were <15 mg kg −1 while mean concentrations in hoovered dusts ( n  = 14) were more variable; specifically, mean Pb dust concentrations ranged from ∼20 to 140 mg kg −1 in 13 samples but was ∼4500 mg kg −1 in a property that had recently undergone extensive renovation. Although mean concentrations of Pb in lint or dust were not related to median Pb concentrations in paint, a strong correlation between barium (Ba) and Pb in dusts suggests that paint is the main source of dust Pb. This study indicates that, in most cases, leaded paints historically applied to interior surfaces have been over-coated and pose little risk, provided that surface coatings are in good condition. However, inappropriate practices during renovation can result in significant contamination of dusts. Our findings are likely to be more broadly applicable to the urban rented sector in the UK and landlords and tenants should, therefore, be made aware of government guidance on the safe decoration or remodelling of older properties where leaded paint is pervasive. Graphical abstract: Image 1 Highlights: XRF was used to measure Pb in painted surfaces and dusts from rented properties in Plymouth. Pb was detected in one-half of interior and exterior surfaces (range = 157 to 139, 000 mg kg −1 ). Depth analysis of Pb revealed that leaded paint had usually been overpainted. The maximum dust concentration (∼4500 mg kg −1 ) was found in a property recently renovated. Pb does not pose a risk unless paint is disturbed during renovation.